Complete IRAC Mapping of the CFHTLS-DEEP, MUSYC, and NMBS-II Fields. (12th November 2018) - Annunziatella, Marianna; Marchesini, Danilo; Stefanon, Mauro; Muzzin, Adam; Lange-Vagle, Daniel; Cybulski, Ryan; Labbe, Ivo; Kado-Fong, Erin; Bezanson, Rachel; Brammer, Gabriel; Herrera, David; Lundgren, Britt; et al.
Abstract: The IRAC mapping of the NMBS-II fields program is an imaging survey at 3.6 and 4.5 μ m with the Spitzer Infrared Array Camera (IRAC). The observations cover three Canada–France–Hawaii Telescope Legacy Survey Deep (CFHTLS-D) fields, including one also imaged by AEGIS, and two MUSYC fields. These are then combined with archival data from all previous programs into deep mosaics. The resulting imaging covers a combined area of about 3 deg 2, with at least ∼2 hr integration time for each field. In this work, we present our data reduction techniques and document the resulting coverage maps at 3.6 and 4.5 μ m. All of the images are W-registered to the reference image, which is either the z-band stack image of the 25% best-seeing images from the CFHTLS-D for CFHTLS-D1, CFHTLS-D3, and CFHTLS-D4, or the K-band images obtained at the Blanco 4-m telescope at CTIO for MUSYC1030 and MUSYC1255. We make all images and coverage maps described here publicly available via the Spitzer Science Center.